Potency Pineapple Skin (Ananas comosus) As Bioadsorbents Reducing Iron (Fe) Levels in Well Water - anwar, khairil; Pamabel, Amanda Atma; Agustini, Medita Tri (Insights in Public Health Journal, 2023)
Pollution water is Wrong One problem biggest Which faced man. Quality water very important for well-being man. According to Organization Health World (WHO), around 829,000 death caused by quality water Which bad every the year . One of the parameters that must meet the standard candy is iron (Fe) Which No more from 1 mg/L. Rate Fe Which more from 1 mg/L will cause health problems. Study This aims to know the rate of reduction in levels of iron (Fe) in dug well water by utilizing waste skin pineapple as bioadsorbent. Type Study This is true experiment with posttest-only control research design group. There are 7 groups with each treatment design done 4 time repetition. Analysis data Which used that is one-way anova. Dug well water was treated by contacting it with various doses adsorbent (1.5 g, 2.0 g and 2.5 g) and time variations (30 minutes and 60 minutes) each in 100 mL water well dig. Results study show flat- the average decrease in iron (Fe) levels in dug well water K (control) 0.5247 mg/L, A (1.5g in 30 minutes) the average reduction is 0.0839 mg/L, B (1.5 g in 60 minutes) average the decline 0.8 5 mg/L, C (2,0 g in 30 minute) average the decrease was 0.10 mg/L, D (2.0 g in 60 min ) the average decrease 0.11 mg/L, E (2.5 g in 30 minutes) the average reduction is 0.0 4 mg/L, and F (2,5 grams in 60 minute) average the decline 0.12 mg /L. Conclusion study This optimal treatment in lowering Fe ie dose 2.5 g with a contact time of 30 minutes . Keywords : Wells _ dig , Pineapple Skin , adsorbent , Substance Iron (Fe)